Chemical bonds [electronic resource] - Manning, Phillip , 1936- (New York : Chelsea House, 2009)
Examines the nature of the chemical bonds, answering questions about how they form, how they are broken, and how they help define life as we know it.
1. Stardust -- 2. Electrons -- 3. Getting together -- 4. Ionic bonds -- 5. Sharing electrons -- 6. The covalent bond -- 7. The metallic bond -- 8. Intermolecular bonding
Description based on print version record
Includes bibliographical references (p. 120-127) and index
Keywords: Chemical bonds; Chemistry; Science